PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI DAN UKM PROVINSI SUMATERA BARAT - Nazaruddinaziz Nazaruddinaziz; Dina Mulia (LP2M Universitas Bina Bangsa, 2022)
This study aims to examine the effect of work environment, work discipline and work motivation at the office of cooperatives and SMES in west Sumatra Province. The technique used in sampling using total sampling technique with the number of respondents as many as 67 people. By testing the hypothesis using quantitative methods, the data obtained in this study will be analyzed using statistics or SPSS (statical program of social science). The result show that the work environment has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee and performance anf work motivation has a positive effect on employee performance